Structural optimization based design of jacket type sub-structures for 10 MW offshore wind turbines - Natarajan, Anand; Stolpe, Mathias; Njomo Wandji, Wilfried (Ocean engineering, 2019)
The design of offshore support structures for wind turbines of 10 MW capacity presents a challenge due to potential resonance problems from the low rotor speeds during operation. The present work delineates the optimization based design of jacket type sub-structures at 50 m water depths for a 10 MW turbine by exploring the frequency constraint space of the sub-structure and confirming feasibility of a cost effective design away from rotor excitation. The conceptual design is made using a two-level optimization framework. The outer design problem, i.e. overall jacket dimensioning, is solved by a derivative free optimization method. The inner problem which consists of member sizing is solved using a robust and efficient Sequential Quadratic Programming method. The objective of the optimization is innovatively chosen as to minimize the fundamental natural frequency of the structure, while subject to frequency constraints, tower top displacement constraints and member ultimate stress constraints. The resulting design is modified during the process of verifying that all ultimate and fatigue limit states are met using fully coupled aero-hydro-elastic simulations. The final design is a low mass four-legged jacket that fully complies with offshore structural standard requirements for all design limit states, while not being affected by rotor excitation, thus being best suited for long operating life.